Track effect: Unraveling the enhancement of college students' autonomous learning by using a flipped classroom approach. Issue 5 (3rd September 2018) - Xiao, Li; Larkins, Randy; Meng, Lijun
ABSTRACT: College students' autonomous learning (AL) is becoming more important in the information era. The flipped classroom model is gaining great attention, for it is viewed as one of the most effective teaching strategies for accelerating students' AL. Undoubtedly, educators play a significant role in this process. Using a sociocultural lens, this qualitative case study focused on the complex and holistic nature of enhancing college students' AL and explored the mechanism and routines to improve their AL using a flipped teaching model. Qualitative interviews from 8 teachers about their experiences in improving students' AL in flipped classes, in addition to observations in both classrooms and teacher education workshops, and related artefacts, were collected and analysed by constant comparative coding. From this evidence, a TRACK effect model was constructed and presented via a visual circle to explain how college students gradually develop AL in a flipped classroom with scaffolds offered by their instructors.